A Review of the Current State of Liver Transplantation Disparities. Issue 3 (12th March 2021) - Wahid, Nabeel A.; Rosenblatt, Russell; Brown, Robert S.
Abstract : Equity in access is one of the core goals of the Organ Procurement and Transplant Network (OPTN). However, disparities in liver transplantation have been described since the passage of the National Organ Transplant Act, which established OPTN in the 1980s. During the past few decades, several efforts have been made by the United Network for Organ Sharing (UNOS) to address disparities in liver transplantation with notable improvements in many areas. Nonetheless, disparities have persisted across insurance type, sex, race/ethnicity, geographic area, and age. African Americans have lower rates of referral to transplant centers, females have lower rates of transplantation from the liver waiting list than males, and public insurance is associated with worse posttransplant outcomes than private insurance. In addition, pediatric candidates and older adults have a disadvantage on the liver transplant waiting list, and there are widespread regional disparities in transplantation. Given the large degree of inequity in liver transplantation, there is a tremendous need for studies to propose and model policy changes that may make the liver transplant system more just and equitable. Abstract : https://www.wileyhealthlearning.com/Activity2/7277057/Activity.aspx?parentActivityId=0